Biocomputational Mapping Of Intraspecies Evolutionary Distances Using Geographical Information System (Applied Biological Research, 2018)
The evolutionary distances from an individual to other individuals of  the same plant species were mapped in geographical information system (GIS). To do this, the relationship between the intraspecies  evolutionary distances and the bioclimatic, geographic and elevation  distances were determined for 17 plant species through multiple linear  regression (MLR). Evolutionary distances were calculated by  constructing Neighbor-joining and Maximum likelihood-based  phylogenetic tree. Power, inverse-power, log10 and Box-Cox  transformations were used for both evolutionary and environmental  distances. The use of bioclimatic, geographic and elevation predictors  and power transformation for MLR models resulted in explaining  more than 60% of variation in intraspecies evolutionary distances for  12 plant species. Power transformation method was more effective  than other methods for increasing models R2. Comparison of MLR  and distance-based redundancy analysis (db-RDA) indicated the  efficiency of MLR in predicting intraspecies evolutionary distances  based on environmental distances.
Keywords: db-RDA; GIS; intraspecies evolutionary distance; power transformation